TOTAL REGRESSION OF ACQUIRED RETINAL ASTROCYTOMA USING PHOTODYNAMIC THERAPY. Issue Volume 10:Issues 1(2016:Winter) (2016) - House, Robert J.; Mashayekhi, Arman; Shields, Jerry A.; Shields, Carol L.
Abstract : Purpose: To report successful treatment of a fine-needle aspiration biopsy–proven acquired retinal astrocytoma with photodynamic therapy. Methods: Case report. Results: A 50-year-old man complaining of decreased vision of his right eye was found to have a visual acuity of 20/100 and an amelanotic juxtapapillary retinal tumor with surrounding subretinal fluid and lipid exudation extending into the fovea. Fine-needle aspiration biopsy showed an astrocytic lesion consistent with retinal astrocytoma. The lesion was treated with one session of photodynamic therapy. At 20 months after photodynamic therapy, visual acuity had improved to 20/20 with complete tumor regression and normal foveal contour on optical coherence tomography. Conclusion: This report confirms that photodynamic therapy of symptomatic acquired retinal astrocytoma may be effective in causing tumor regression and stabilizing or improving visual acuity by reducing tumor leakage. Abstract : A 50-year-old man with a visual acuity of 20/100 from an acquired juxtapapillary retinal astrocytoma, confirmed by needle biopsy, was treated with photodynamic therapy. Twenty months later, the best-corrected visual acuity had improved to 20/20 with complete tumor regression and complete resorption of subretinal fluid.